The Reception of Society Towards Hoax News About the Covid-19 Pandemic on TikTok: Resepsi Masyarakat Terhadap Berita Hoax Tentang Pandemi Covid-19 di tiktok - Afdianto, Irfan; Abadi, Totok Wahyu (Universitas Muhammadiyah Sidoarjo, 2023)
This research aims to analyze and explain the reception of society towards hoax news about the Covid-19 pandemic on TikTok. A quantitative descriptive method was employed, drawing on Jalaluddin Rahkmat's perception theory (1989:51). The study focused on the village of Cangkring Sidokare, with 96 respondents participating. The findings indicate that concerning the news item